The Effect of Hatha Yoga on Psychoemotional Characteristics in Healthy Subjects - Eglė Kasparavičiūtė; Laimonas Šiupšinskas; Jonas Poderys (Lithuanian Sports University, 2018)
Research background and hypothesis. There is a lack of evidence-based information about the effect of hatha yoga on psychoemotional characteristics of healthy people in recent scientific papers. Most of the researchers use self-reported methods to evaluate psychoemotional factors. We used objective method to find out what kind of effect could be found on psychoemotional characteristics of yoga practitioners. Hypothesis: hatha yoga practice has different effect on psychoemotional characteristics in beginners and advanced yoga practitioners. Research aim was to evaluate the effect of hatha yoga on psychomotoric tone, extra-introversity, aggression, emotional lability and anxiety in healthy subjects. Research  methods.  40  healthy  persons  with  no  reported  diseases  participated  in  the  research.  Participants were  divided  into  two  groups:  beginners  (practicing  yoga  for  not  more  than  one  year,  n  =  22)  and  advanced (practicing yoga for at least two years, n = 18) yoga practitioners. Psychoemotional characteristics: inborn and present psychomotoric tone, extra-introversity, aggression, emotional lability and anxiety were measured using the Myokinetic Psyhodiagnosis of D. Emilio Mira (Simon, 1943) test. The research data was compared with standard limits and between the beginners and advanced yoga practitioners groups. Research results. Hatha yoga had general effect on psychoemotional status in the beginners and advanced yoga practitioners. Psychomotoric tone increased and emotional lability decreased in both groups (p < 0.05). Psychomotoric tone, extra-introversity and emotional lability were within the standard limits. Anxiety and aggression were lower in both groups in 6-months period. Aggression and emotional lability in the beginners' group was lower compared to those in the advanced yoga group (p < 0.05). Discussion and conclusions. Almost all psychoemotional characteristics were within the standard limits in both groups of yoga practitioners. The bigger effect of hatha yoga was found in the yoga beginners' group. The evidence- based information in scientific literature about the effect of yoga on psychoemotional characteristics with objective measures is still missing. Keywords: hatha yoga, psychomotoric test, psychoemotional characteristics.